The evolution of brain structure captured in stereotyped cell count and cell type distributions - Němec, Pavel; Osten, Pavel (Current opinion in neurobiology, 2020)
The stereotyped features of brain structure, such as the distribution, morphology and connectivity of neuronal cell types across brain areas, are those most likely to explain the remarkable capacity of the brain to process information and govern behaviors. Recent advances in anatomical methods, including the simple but versatile isotropic fractionator and several whole-brain labeling, clearing and microscopy methods, have opened the door to an exciting new era in comparative brain anatomy, one that has the potential to transform our understanding of the brain structure-function relationship by representing the evolution of brain complexity in quantitative anatomical features shared across species and species-specific or clade-specific. Here we discuss these methods and their application to mapping brain cell count and cell type distributions-two particularly powerful neural correlates of vertebrate cognitive and behavioral capabilities.
Keywords: Species Specificity; Brain Mapping; mozek; Animals; počet buněk; druhová specificita; mapování mozku; Brain; neurony; Cell Count; zvířata; Neurons